PENINGKATAN KETERAMPILAN MENULIS PUISI BEBAS MELALUI MODEL PEMBELAJARAN EXPERIENTIAL LEARNING BERBANTUAN MEDIA GAMBAR - Yusi Yustisian Adlah (LP2M UIN Abdul Muthalib Sangadji Ambon, 2025)
The ability to write free verse poetry among junior high school students remains relatively low due to the limited variety of instructional models that can stimulate creativity and meaningful learning experiences. This condition indicates the urgency of applying more active and contextual learning models. This study aims to evaluate the effectiveness of the experiential learning model assisted by picture media in improving the free verse writing skills of eighth-grade students at SMPN Satu Atap Cikawao, Sumedang. The research employed a pretest–posttest control group design by comparing the learning outcomes of the experimental and control groups.The results show that the experimental group experienced a more significant improvement than the control group. The writing scores of students in the experimental group increased from 5.6435 to 7.7739 (an improvement of 2.1304), whereas the control group increased from 5.4533 to 7.0200 (an improvement of 1.5667). In addition, students responded positively to the use of picture media as a stimulus for creativity. These findings confirm that the experiential learning model assisted by picture media is effective in enhancing skills for writing free verse poetry.This study contributes to enriching instructional strategies in Indonesian language learning, particularly in developing creative writing skills. Further studies are recommended to apply this model at different grade levels or school contexts and to examine the integration of other visual media to obtain more comprehensive results.